Hot Off the Press: SGEM #257—EMTALA: It's the Law of the Land. (4th July 2019) - Heitz, Corey; Morgenstern, Justin; Bond, Christopher; Milne, William K.
Abstract: The Office of the Inspector General has the authority to levy fines relating to violations of the Emergency Medicine Treatment and Labor Act (EMTALA) for both medical and psychiatric care. Terp et al. have described the incidence of violations and penalties levied for psychiatric cases and compared them to that for medical. This article reviews that article and the podcast recorded with Dr. Terp and the ensuing discussion in the podcast and online.